(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
Overhead tank are generally classified as Ordinary Moment Resisting Frame (OMRF) and Special Moment Resisting Frame (SMRF) supported response reduction factor. Generally, the Overhead tank consists of structural members like slabs, beams, columns, and footings, where the subjected loads are transferred between the structural members and eventually transferred to the Sub-grade of the soil. The behavior of the Overhead tank is different for various sorts of loadings(Dead, Live, Wind, and Seismic) within the analysis and of overhead tank usefully Indian standards codes suggest various loads combinations supported probability of Occurrence. There are around 52 load combinations and IS codes suggest the lateral load (wind and seismic) acts independently but the load governing the planning of structural members is to be acknowledged. and therefore the present study to research the consequences of wind and seismic forces on Overhead tank structures of heights (15m) are considered in seismic zones II, III, IV, V where length and width of the structures are kept constant. An earthquake load is calculated as per IS and wind pressure calculated as per IS 875-1987. The analysis is done the use of STAAD.pro software.